2019
DOI: 10.5897/ajar2018.13687
|View full text |Cite
|
Sign up to set email alerts
|

Seed treatment and pre-inoculation of soybean: effect of storage period and agrochemicals on the physiological quality of seed and yield

Abstract: Industrial seed treatment of soybean [Glycine max (L.) Merr.] has increased over the last years. New technologies have been developed to allow the inoculation procedure, which is traditionally done at the day of sowing, to be performed with the industrial treatment days or even weeks before sowing. Since little is known about the compatibility of agrochemicals and pre-inoculation, the objective of this study was to determine whether the storage period and the combination of fungicides and insecticides could ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Sandini et al [43] indicated that some combinations of fungicides and insecticides may adversely affect the physiological quality of seeds stored for up to 51 days before sowing, but none of them questioned the formation of nodules involving B. elkanii and soybean yield in field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Sandini et al [43] indicated that some combinations of fungicides and insecticides may adversely affect the physiological quality of seeds stored for up to 51 days before sowing, but none of them questioned the formation of nodules involving B. elkanii and soybean yield in field conditions.…”
Section: Discussionmentioning
confidence: 99%